Increasing solvency by moderating social capital: a study on group lending model from community empowerment trust fund – Indonesia - Indriani, Etty; Irawan, Nico; Hartawan; Khristiana, Yenni (Business: Theory and Practice, 2023)
The Community Empowerment Trust Fund is a revolving fund belonging to the community originating from the former Sub-District Development Program and the National Program for Independent Rural Community Empowerment in Indonesia which ended in 2014. Community institutions then manage the Community Empowerment Trust Fund to fund community economic activities in the form of group loans. The group lending model is a financial inclusion that reaches the poor who do not have collateral. These funds have been managed well with the group loan model. However, the success of managing these funds cannot be separated from the social capital built between group members and between the group and the fund management unit. This study aims to examine the management of the borrower group – group internal setting; group loan appraisal and group loan control – and social capital on repayment performance. The study results prove that group lending appraisal, group lending control, and social capital positively impact repayment capacity. The research finding is social capital strengthens group lending control dynamics to increase repayment capacity. Another finding explains that women’s loan groups have a higher collectability rate in repayment of loans compared to productive economic business groups whose members are both male and female.